Regulation of GABA Neurotransmission by Glutamic Acid Decarboxylase (GAD) - Pravinchandra Modi, Jigar; Prentice, Howard; Wu, Jang-Yen (Current Pharmaceutical Design, 2015)
Control of GABA neurotransmission at the pre-synaptic site occurs substantially through the activation of the glutamic acid decarboxylase (GAD) enzymes GAD65 and GAD67. Concentrations of GAD65 and GAD67 are controlled either by transcription or by mRNA splicing and importantly the activities of these key enzymes are regulated by post-translational mechanisms. Important post-translational modifications include proteolytic cleavage, phosphorylation and palmitoylation. A truncated form of GAD65 (tGAD65) is more active than full length GAD65 (fGAD65) whereas, by contrast, truncated GAD67 (tGAD67) is less active than full length GAD67 (fGAD67). The protein responsible for cleaving of fGAD65 and fGAD67 is mu-calpain. GABA neurotransmission is dependent upon whether GAD is associated with synaptic vesicles (SV) and calpain performs a vital role by generating the highly active tGAD65 resulting in augmented GABA synthesis and wrapping uptake into SV. Studies on GAD phosphorylation demonstrate that GAD65 is regulated through phosphorylation by PKC while GAD67 is inhibited through phosphorylation by PKA. Cysteine residues 455 and 446 in GAD67 and GAD65 individually are critical for full GAD regulation. Interaction with the cofactor pyridoxal 50-phosphate (PLP) at this these respective locations regulate the switch between PLP-bound active holoGAD and an unbound active apoGAD form. Transient switching to the PLP bound active holoGAD is integral to GABA neurotransmission. Specific to GAD65 but not GAD67 is palmitoylation by HIP14 which facilitates GAD65 anchoring to SV and enhances the contribution of vesicular GABA to neurotransmission. From studies on a rodent stroke model calpain-mediated cleavage of GAD enzyme has been shown to occur under pathological conditions resulting in less SV refilling and depletion of existing pools of SV releasable GABA.
Keywords: Glutamic acid decarboxylase